2017
DOI: 10.1016/j.chb.2016.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Combined reality therapy and mindfulness meditation decrease intertemporal decisional impulsivity in young adults with Internet gaming disorder

Abstract: Decisional impulsivity represents an important phenotype and a therapeutic target in Internet gaming disorder (IGD). Reality therapy and mindfulness meditation were two approaches to reduce impulsivity. This study aimed to evaluate the efficacy of a group behavioral intervention combining reality therapy and mindfulness meditation in reducing decisional impulsivity and IGD severity. Twenty-five IGD and 21 healthy comparison (HC) young adults participated in baseline tests on the delay discounting and balloon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 58 publications
(78 reference statements)
2
70
0
1
Order By: Relevance
“…Regarding the geographic characteristics of the included studies, nine were from China (Ding et al 2014;Du et al 2016;Du et al 2017;Hu et al 2017;Tian et al 2018;Wang et al 2016Wang et al ,2017Wu et al 2018;Yao et al 2017), eight were from South Korea (Choi et al 2014;Hyun et al 2015;Kim et al 2017a;Kim et al 2017b;Lee et al 2017;Lee et al 2017;Rho et al 2017;Ryu et al 2018), three were from Germany (Rehbein et al 2010;Sariyska et al 2017;Walther et al 2012), two were from Australia (Bailey et al 2013;Metcalf and Pammer 2014), two were from Singapore (Gentile et al 2011;Liau et al 2015), two were from the USA (Bargeron and Hormes 2017; Stockdale and Coyne 2018), one was from Spain (Irles and Gomis 2016), one was from the UK (Irvine et al 2013), one was from Belgium (Deleuze et al 2017), one was from the Czech Republic (Blinka et al 2016), and one was from Taiwan (Yen et al 2017). Additionally, there were two cross-cultural studies.…”
Section: Country In Which the Data Were Collectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the geographic characteristics of the included studies, nine were from China (Ding et al 2014;Du et al 2016;Du et al 2017;Hu et al 2017;Tian et al 2018;Wang et al 2016Wang et al ,2017Wu et al 2018;Yao et al 2017), eight were from South Korea (Choi et al 2014;Hyun et al 2015;Kim et al 2017a;Kim et al 2017b;Lee et al 2017;Lee et al 2017;Rho et al 2017;Ryu et al 2018), three were from Germany (Rehbein et al 2010;Sariyska et al 2017;Walther et al 2012), two were from Australia (Bailey et al 2013;Metcalf and Pammer 2014), two were from Singapore (Gentile et al 2011;Liau et al 2015), two were from the USA (Bargeron and Hormes 2017; Stockdale and Coyne 2018), one was from Spain (Irles and Gomis 2016), one was from the UK (Irvine et al 2013), one was from Belgium (Deleuze et al 2017), one was from the Czech Republic (Blinka et al 2016), and one was from Taiwan (Yen et al 2017). Additionally, there were two cross-cultural studies.…”
Section: Country In Which the Data Were Collectedmentioning
confidence: 99%
“…The vast majority of studies recruited more male participants (n = 12,492; 70.1%) than female participants (n = 5333; 29.9%). No information was provided about the participants' gender in two studies (Bargeron and Hormes 2017;Yao et al 2017) in order to avoid the activation of gender-related stereotypes (Bargeron and Hormes 2017). Twenty-four studies included adult samples and nine studies included adolescent samples (Ding et al 2014;Du et al 2016;Du et al 2017;Irles and Gomis 2016;Hu et al 2017;Liau et al 2015;Rehbein et al 2010;Tian et al 2018;Walther et al 2012).…”
Section: Participantsmentioning
confidence: 99%
“…The correlation between negative affect and gambling craving has also been revealed in GD (de Castro et al, 2007), and the negative affect along with craving as treatment outcome have been demonstrated the sensitivity to pharmacological treatment (Fong et al, 2008). Accumulating evidence suggests co-occurrence of IGD and negative affective experience (e.g., depression; Meng et al, 2014; Zhang et al, 2015; Yao et al, 2017), with a preliminary intervention using mindfulness meditation found its effect in reduction of negative affect (Yao et al, 2017). Further, evidence from intervention indicates that mindfulness-based interventions have been demonstrated efficacy for craving reductions mainly through alleviating negative emotional states (e.g., depression and anxiety; ?…”
Section: Introductionmentioning
confidence: 99%
“…Studies among IGD participants have implicated the relationship between dysfunction of inhibition control and addictive behaviors (Meng et al, 2014; Yao et al, 2015), and preliminarily demonstrated the effects of combined reality therapy and mindfulness meditation in reduction of decisional impulsivity (Yao et al, 2017). Further, evidence from neural studies highlighted the imbalance between the brain cognitive system and reward system in addiction (Volkow and Baler, 2014), which lead to inability of the individual to suppress aggressive thoughts and impulsive aggressive behavior (George and Koob, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that school-based group using cognitive behavioral theory (CBT) was effective in reducing IA [51]. Other studies also reported that reality therapy counselling [52], reality therapy combined with mindfulness mediation [53], and motivational interviewing [54,55] were effective in reducing PIU. Findings also suggest that reducing participants' depressive symptoms may be a useful strategy for reducing smoking.…”
Section: Implications For Practicementioning
confidence: 99%